The Effectiveness of Alphabet Block Games on Language Development in Early Childhood Letter Recognition: Efektivitas Permainan Balok Huruf terhadap Perkembangan Bahasa dalam Pengenalan Huruf Anak Usia Dini - Noviana Noviana; Baiq Halimatuz Zuhrotul; Muh. Zakaria (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
Language ability is a fundamental aspect of early childhood development, especially letter recognition, which serves as the foundation for literacy skills. Preliminary observations at KB Nune Pangeran indicated that most children in Group B struggled with recognizing letters due to conventional teaching methods that relied heavily on worksheets and lacked engaging media. This study aimed to examine the effectiveness of using letter block games to improve children’s language development, particularly in early literacy. The research employed a Classroom Action Research (CAR) design based on Kemmis and McTaggart’s model, conducted in two cycles involving 24 children aged 5–6 years during the 2024/2025 academic year. Data were collected through structured observation using validated instruments assessed by expert judgment. The findings revealed a clear improvement in children’s performance across the cycles, with the majority reaching the “Developing as Expected” and “Very Well Developed” categories by the second cycle. These results suggest that letter block games provide meaningful, concrete, and enjoyable learning experiences that significantly enhance early literacy development. The study contributes to the literature by emphasizing the pedagogical value of manipulative learning media and supports theoretical perspectives such as Vygotsky’s scaffolding and Bruner’s enactive representation. This research highlights the potential of simple educational games to enrich early childhood education and offers practical implications for teachers and institutions seeking innovative literacy strategies.